The negative impact of the psychiatric model of chronic fatigue syndrome on doctors' understanding and management of the illness. Issue 3 (2nd July 2020) - Geraghty, Keith
ABSTRACT: Background: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a disabling condition that greatly impacts the lives of sufferers. Many sufferers report problems getting a confirmatory diagnosis and difficulties getting doctors to believe them and offer support. Objective: This paper explores this issue by examining a biopsychosocial (BPS) model of ME/CFS promoted within psychiatry and its potential influence on how doctors might view and manage the illness. Method: A narrative literature review is undertaken to identify salient theory and discourse for consideration. Findings: Psychiatrists proffer a hypothetical model of ME/CFS aetiology and continuance, that instructs doctors to view the illness as a syndrome perpetuated by psycho-social factors that sustain unexplained symptoms such as fatigue, pain and post-exertional malaise, rather than symptoms being related to biological disease processes. The psychiatric model theorises that patients' symptoms are maintained by their maladaptive beliefs and behaviours, requiring psychotherapy. Conclusion: The psychiatric BPS model of ME/CFS may negatively bias how physicians approach the illness, with doctors directed to view patients' complaints as manifestations of psychological distress, rather than physical symptoms that require medical investigation or intervention. This finding may help explain why many ME/CFS patients feel disbelieved and unsupported after seeking medical care. Psychiatric theory fails to acknowledge or incorporate a substantial body of evidence showing biological deficits associated with ME/CFS. Medical trainees and physicians need more training and clinical exposure to ME/CFS patients, armed with better awareness of misleading and unproven claims associated with the BPS model.